Gene expression changes in human prostate carcinoma cells exposed to genotoxic and nongenotoxic aryl hydrocarbon receptor ligands - Hrubá, Eva; Vondráček, Jan; Líbalová, Helena; Topinka, Jan; Bryja, Vítězslav; Souček, Karel; Machala, Miroslav (Toxicology letters, 2011)
Carcinogenic polycyclic aromatic hydrocarbons (PAHs) are known as efficient mutagens and ligands of the aryl hydrocarbon receptor (AhR), which has been suggested to play an important role in prostate carcinogenesis. In order to evaluate the complex relationship between the genotoxicity and the AhR-mediated activity of PAHs in prostate cells, we selected benzo[a]pyrene (BaP) and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), as model genotoxic and nongenotoxic AhR ligands, respectively, to explore global changes in gene expression in LNCaP cells by microarray analysis. We identified 112 genes that were differentially expressed in cells treated for 24h with BaP, TCDD or both compounds. Our data indicated that the impacts of BaP and TCDD on transcriptome of LNCaP cells significantly overlap, since over 64% of significantly up-regulated genes and 47% of down-regulated genes were similarly affected by both AhR ligands. This suggested that the activation of AhR played a prominent role in the nongenotoxic effects of BaP in the prostate carcinoma cell model LNCaP. Both AhR ligands suppressed expression of genes associated with cell cycle progression, DNA replication, spindle assembly checkpoint or DNA repair, which probably occurred secondary to inhibition of cell cycle progression. In contrast, we identified Wnt5a, an important regulator of prostate cancer progression, to be induced as early as 6h after exposure to both AhR ligands. The AhR ligand-induced Wnt5a upregulation, together with other observed alterations of gene expression, may further contribute to enhanced cell plasticity of prostate carcinoma cells.
Keywords: mutageny; Cell Cycle; nádorové buněčné linie; Gene Expression Profiling; ligandy; Carcinogens, Environmental; Male; protein Wnt 5a; regulace genové exprese u nádorů; DNA Replication; Time Factors; replikace DNA; mužské pohlaví; nádory prostaty; Polychlorinated Dibenzodioxins; Proto-Oncogene Proteins; Receptors, Aryl Hydrocarbon; Cell Line, Tumor; Spindle Apparatus; Mutagens; buněčný cyklus; Benzo(a)pyrene; aparát dělícího vřeténka; Carcinoma; Ligands; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Prostatic Neoplasms; Humans; Gene Expression Regulation, Neoplastic; oprava DNA; benzopyren; časové faktory; protoonkogenní proteiny; Wnt-5a Protein; stanovení celkové genové exprese; polychlorované dibenzodioxiny; Oligonucleotide Array Sequence Analysis; receptory aromatických uhlovodíků; DNA Repair; Wnt Proteins; karcinogeny životního prostředí; lidé; proteiny Wnt; karcinom